Clinical and MRI differential analysis of autoimmune encephalitis and viral encephalitis. Issue 2 (April 2023) - Tan, Yongming; Liu, Meng; He, Laichang
الملخص: أهداف البحث: تحليل الخصائص السريرية وخصائص التصوير بالرنين المغناطيسي لالتهاب الدماغ المناعي الذاتي والتهاب الدماغ الفيروسي في المرحلة الأولى من ظهور المرض. طرق البحث: التحليل الاستعادي للمظاهر السريرية، والاختبارات المعملية، وفحص مخطط كهربية الدماغ، وفحوصات التصوير ونتائج العلاج لـ ٢٤ حالة التهاب الدماغ الفيروسي و ٢٠ حالة التهاب الدماغ المناعي الذاتي. النتائج: كان عمر بداية مجموعة التهاب الدماغ الفيروسي أصغر بكثير من مجموعة التهاب الدماغ المناعي الذاتي، وخاصة في المراهقين. كانت نسبة الحمى والصداع والقيء في مجموعة التهاب الدماغ الفيروسي أعلى من تلك الموجودة في مجموعة التهاب الدماغ المناعي الذاتي، وهناك مظاهر قليلة لنقص التهوية المركزية. كان معدل الإصابة غير الطبيعي لإنزيمات عضلة القلب في مجموعة التهاب الدماغ الفيروسي أعلى بكثير من تلك الموجودة في مجموعة التهاب الدماغ المناعي الذاتي. لم يكن هناك فرق كبير في مخطط كهربية الدماغ بين مجموعة التهاب الدماغ الفيروسي ومجموعة التهاب الدماغ المناعي الذاتي. بالنسبة لفحص التصوير، كانت نسبة الآفة المفردة التي تنطوي على فص واحد أو عدم تناسق متعدد في الجهاز الحوفي في مجموعة التهاب الدماغ الفيروسي أعلى من تلك الموجودة في مجموعة التهاب الدماغ المناعي الذاتي. كان معدل حدوث تحسين الآفة في مجموعة التهاب الدماغ الفيروسي أعلى من ذلك في مجموعة التهاب الدماغ المناعي الذاتي، وفي الوقت نفسه، كان تسلسل التصوير الموزون بالانتشار أكثر حساسية من تسلسل ترميم انعكاس التوهين السائل تي ٢ في الكشف وتقييم الفعالية ومراجعة المتابعة لمجموعة التهاب الدماغ المناعي الذاتي ومجموعة التهاب الدماغ الفيروسي. الاستنتاجات: سن بداية التهاب الدماغ الفيروسي أصغر، والأعراض السريرية لالتهاب الدماغ المناعي الذاتي والتهاب الدماغ الفيروسي مختلفة مع دلالة إحصائية. يمكن أن يعكس التصوير بالرنين المغناطيسي بشكل موضوعي خصائص التصوير لكلا المجموعتين. يمكن أن يؤدي الجمع بين المظاهر السريرية المبكرة ومظاهر التصوير إلى التشخيص والعلاج المبكر، وتحسين الإنذار. Abstract: Objectives: The goal of this study was to analyze the clinical and magnetic resonance imaging (MRI) characteristics of autoimmune encephalitis (AE) and viral encephalitis (VE) at the initial stage of onset. Methods: This study was a retrospective analysis of the clinical manifestations, laboratory tests, electroencephalogram examination, imaging examinations, and treatment outcomes of 24 VE patients and 20 AE patients. Results: The onset age was significantly younger in the VE group than in the AE group, mainly occurring in adolescents (P < 0.05). The proportions of fever, headache, and vomiting were higher in the VE group than in the AE group (P < 0.05), and there were few manifestations of central hypoventilation. The incidence of abnormal myocardial enzymes was significantly higher in the VE group than in the AE group (P < 0.05). There was no significant difference in electroencephalogram test results between the VE and AE groups. Regarding magnetic resonance imaging (MRI), the proportion of single lesion involving a single lobe or multiple asymmetries involving the limbic system in the VE group was higher than that in the AE group (P < 0.05). The incidence of lesion enhancement in the VE group was higher than that in the AE group. Meanwhile, diffusion-weighted imaging sequence was more sensitive than T2 liquid-attenuated inversion recovery sequence in the detection, efficacy evaluation, and follow-up review of the AE and VE groups. Conclusion: The onset age of VE is younger, and the clinical symptoms of AE and VE differ with statistical significance. MRI can objectively reflect the imaging characteristics of both groups. Combining early clinical manifestations with imaging manifestations can facilitate early diagnosis and treatment, and improve the prognosis.